Early and mid-term efficacy of volar titanium lock plate applications in radial distal intraarticular fractures - Bangin Bekir Candan (Acta Medica Alanya, 2019)
Aim: The aim of the study is to determine the efficacy of the functional and radiological results of the pa-tients who underwent titanium volar locking plaque in adult distal radius fractures with early and mid-term analysis. Patients and methods: 64 patients (67 fractured limbs) who underwent volar locking plate due to distal radius fracture were retrospectively analyzed. The mean age was 53.31 (18-75). They were classified according to the Frkyman classification and AO classification. The modified Gartlant Werley Score, Disability of the Arm, and Hand (DASH) score were evaluated according to Modified Stewart scoring system. Results: According to Modified Gartland-Werley Score, 35 (52.2%) were evaluated as excellent, 27 (39.7%) as good, 4 (5.9%) as moderate and 1 (1.5%) as poor. The mean value of DASH score was 9.5 ± 8.8 (0-35). Palmar slope preoperatively was -5.58 ± 14.9 [(-50) - (30)], postoperatively 3.65 ± 10.88 [(- 30) - (+ 45)]. Radial height, radial inclination and palmar slope were significantly improved (p = 0.001). When Stewart radiological score was evaluated, 37 (54.4%) were excellent, 26 (38.8%) were as good and 4 (5.9%) as moderate.